Maximizing Learning Potential: Unravelling the Synergy of Blended Learning and Student’s Learning Motivation and Achievement - Bachtiar Bachtiar (Edumaspul: Jurnal Pendidikan, 2023)
Blended learning has been emerging as one of the most popular learning methods used Post Covid -19. Blended learning is the learning process that integrates face-to-face learning and online learning. This article aims to investigate the dynamic relationship between blended learning and students' learning motivation and achievement in English language subject. The participants were 150 11th grade students from two junior high schools in Polman district who had experienced in using blended learning. This study used mixed methods by employing two research tools, namely questionnaire and semi-structured interviews. The research findings suggest a highly positive relationship between blended learning and student learning motivation and learning achievement. some key factors within blended learning environments that contribute to enhancing their motivation. These factors include the flexibility and adaptability of blended learning designs. The study results also showed the dynamic relationship between students’ learning motivation and their engagement and achievement in learning. The study results contribute to the dissemination of information to educational stakeholders and academic forums for teachers as input of considering the implementation of blended learning an instruction fit in the current educational settings.